2020
DOI: 10.1111/ecog.05118
|View full text |Cite
|
Sign up to set email alerts
|

Simulation modeling reveals the evolutionary role of landscape shape and species dispersal on genetic variation within a metapopulation

Abstract: Different shapes of landscape boundaries can affect the habitat networks within them and consequently the spatial genetic‐patterns of a metapopulation. In this study, we used a mechanistic framework to evaluate the effects of landscape shape, through watershed elongation, on genetic divergence among populations at the metapopulation scale. Empirical genetic data from four, sympatric stream‐macroinvertebrates having aerial adults were collected from streams in Japan to determine the roles of species‐specific di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…In parallel, theoretical models that address the effect of spatial connectivity of riverine networks on genetic variation (Morrissey & de Kerckhove, 2009 ; Paz‐Vinas & Blanchet, 2015 ; Paz‐Vinas et al, 2015 ), on evolution of dispersal (Henriques‐Silva et al, 2015 ), and emergence of neutral genetic structure (Fronhofer & Altermatt, 2017 ; Stokes & Perron, 2020 ; Thomaz et al, 2016 ) have demonstrated that dispersal along riverine networks has a direct imprint on the genetic structure and diversity of the inhabiting organisms. While these theoretical models provide direct testable predictions, a direct comparison between within‐population genetic diversities estimated from empirical data and predictions from theoretical models assuming an identical riverine network has been largely lacking (but see Chiu, Li, et al, 2020 ; Chiu, Nukazawa, et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…In parallel, theoretical models that address the effect of spatial connectivity of riverine networks on genetic variation (Morrissey & de Kerckhove, 2009 ; Paz‐Vinas & Blanchet, 2015 ; Paz‐Vinas et al, 2015 ), on evolution of dispersal (Henriques‐Silva et al, 2015 ), and emergence of neutral genetic structure (Fronhofer & Altermatt, 2017 ; Stokes & Perron, 2020 ; Thomaz et al, 2016 ) have demonstrated that dispersal along riverine networks has a direct imprint on the genetic structure and diversity of the inhabiting organisms. While these theoretical models provide direct testable predictions, a direct comparison between within‐population genetic diversities estimated from empirical data and predictions from theoretical models assuming an identical riverine network has been largely lacking (but see Chiu, Li, et al, 2020 ; Chiu, Nukazawa, et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Landscape characteristics are a key factor in the population dynamics of most animal species [ 1 , 2 , 3 ]. Their relative influence on population connectivity not only depends on patch configuration, but also on behavioural patterns related to the response of individuals to a given landscape [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…This in turn promotes asymmetric gene flow and a source-sink metapopulation structure (Campbell Grant et al 2007). Consequently, a prevailing trend is for a downstream increase in allelic diversity (Paz-Vinas and Blanchet 2015, Paz-Vinas et al 2015, Blanchet et al 2020), whereas unique genetic variation is most often retained within more peripheral headwater populations (Morrissey and De Kerckhove 2009, Chiu et al 2020b).…”
Section: Introductionmentioning
confidence: 99%